Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/met10060816
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Inducing Compressive Residual Stresses on a Surface by Laser Peening without Coating

Abstract: Laser peening without coating (LPwC) involves irradiating materials covered with water with intense laser pulses to induce compressive residual stress (RS) on a surface. This results in favorable effects, such as fatigue enhancement; however, the mechanism underlying formation of the compressive RS is not fully understood. In general, tensile RS is imparted on the surface of the material due to shrinkage after heating by laser irradiation. In this study, we assessed the thermo-mechanical effect of single laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…In the case of laser beam processing, thermal stresses and phase transition stresses depend mainly on the processing conditions and material properties. Tensile stresses arise after laser remelting of the surface material, while compressive stresses occur when laser treatment takes place without melting [ 43 , 44 ]. The energy density and the speed of the laser beam movement have the greatest influence on the type of resultant residual stress after laser processing [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of laser beam processing, thermal stresses and phase transition stresses depend mainly on the processing conditions and material properties. Tensile stresses arise after laser remelting of the surface material, while compressive stresses occur when laser treatment takes place without melting [ 43 , 44 ]. The energy density and the speed of the laser beam movement have the greatest influence on the type of resultant residual stress after laser processing [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…XRD experiments employing SR spatially resolved the strain and allowed RS mapping showing that, after LPwC, the top surface was compressive [28]. Using these results and an empirical model, we explained how LPwC induced compressive RSs on the top surface [26]. Here, we describe how we visualized fatigue cracks with the aid of SR-based CT and CL, and how we performed time-resolved XRD using an XFEL.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may also induce a negative heat effect on the surface, creating an undesirable tensile RS that competes with the favorable effect of the compressive RS [24,25]. Recently, we summarized the results of a series of XRD experiments using SR and concluded that LPwC induced compressive RSs on top surfaces with the exception of the final laser spot when the irradiating laser pulse density was high and the adjacent laser pulses overlapped appropriately [26]. We took full advantage of valuable SR characteristics (high brilliance and spatial coherence) when precisely mapping RS distributions on top surfaces after single, line, and areal irradiations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the case of the numerical simulation, residual stress distributions due to laser spots were clearly observed [ 6 , 34 , 35 , 36 ]. Recently, the patterns of residual stress on the surface due to laser spots were also observed [ 37 , 38 ]. G. Xu et al measured the residual stress of SUS316L by the sin 2 ψ method, in which the diameter of the measured area was 2 mm with a 0.5 mm step; the laser spot was 3 × 3 mm 2 ; the overlapping rates were 30%, 50% and 70%; and the cyclic pattern of the residual stress was obtained [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…X. Pan et al measured the residual stress of Ti6Al4V by the sin 2 ψ method, in which the diameter of the measuring area was 2 mm with a 1 mm step, the laser spot was 2.4 mm, the overlapping rate was 40% and a cyclic pattern due to laser spots was not observed in the distribution of residual stress [ 39 ]. Using a synchrotron, Y. Sano et al measured the distribution of the residual stress crossing over a single laser spot with 1D line irradiation by measuring an area of 0.2 mm in diameter; the laser spot was about 1 mm in diameter and the authors reported the tensile residual stress due to the laser spot [ 38 ]. It was determined by numerical simulation that the crack propagation was affected by the residual stress distribution due to laser peening [ 40 , 41 ]; therefore, the precise distribution of the residual stress had to be determined.…”
Section: Introductionmentioning
confidence: 99%